Does writing enhance recall and memory consolidation? Revealing the factor of effectiveness of the self‐administered interview. Issue 5 (28th June 2021) - Miura, Hiroshi; Matsuo, Kayo
Summary: The self‐administered interview (SAI©) is a booklet in which eyewitnesses write down their memories of an incident without assistance. The SAI can gather a significant amount of eyewitness information, and completing the SAI soon after witnessing an event can improve later recall. This study aimed to reveal the factor of effectiveness of the SAI and specifically focused on the method of handwriting. Participants watched a video and immediately recalled the event in the three conditions: SAI‐writing, SAI‐speaking, and free recall (speaking). One week later, participants again recalled the event via free recall. The results showed that participants in the SAI‐writing condition reported more correct information than those in the other conditions at both time points. This suggests that a factor of effectiveness of the SAI is the method of writing. Thus, initial written recall using the SAI could facilitate later recall in police investigative interviews.